Escape from X chromosome inactivation and female bias of autoimmune diseases - Mousavi, Mohammad Javad; Mahmoudi, Mahdi; Ghotloo, Somayeh (Molecular medicine (Cambridge, Mass.), 2020)
Generally, autoimmune diseases are more prevalent in females than males. Various predisposing factors, including female sex hormones, X chromosome genes, and the microbiome have been implicated in the female bias of autoimmune diseases. During embryogenesis, one of the X chromosomes in the females is transcriptionally inactivated, in a process called X chromosome inactivation (XCI). This equalizes the impact of two X chromosomes in the females. However, some genes escape from XCI, providing a basis for the dual expression dosage of the given gene in the females. In the present review, the contribution of the escape genes to the female bias of autoimmune diseases will be discussed.